Effectiveness evaluation of the complex medical and psychological method of treating patients with insomnia - A. V. Vasil'eva; T. A. Karavaeva; Yu. P. Kolesova; D. S. Radionov; D. A. Starunskaya; M. V. Fomicheva; S. M. Abdullaeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
This article presents an assessment of the effectiveness of the program for providing medical and psychological care to patients with insomnia, based on psychotherapeutic and psychophysiological approaches, including using a light lamp, biofeedback devices, taking into account clinical and psychological and socio-psychological characteristics, and also evaluates the effectiveness this program. The scientific literature does not describe analogues of the totality of the use of these methods for the contingent of patients with outpatient insomnia. The uniqueness of the developed program lies in its clear algorithmization, the absence of complex techniques of psychological (psychotherapeutic) intervention, which ensures the reproducibility of the program in practical health care institutions if there is a psychotherapist or clinical psychologist on staff who knows the skills of cognitive behavioral therapy and diaphragmatic breathing. The technique has passed clinical testing approved by the Ministry of Health of the Russian Federation (protocol 2020-37-3). The quantitative evaluation of the effectiveness of the method was carried out on seven indicators: (1) Improvement in the subjective characteristics of sleep, (2) Improvement in the quality of sleep, (3) Reduction of the insomnia severity index, (4) Reduction of daytime sleepiness, (5) Reduction of the consequences of sleep disorders, (6) Decreased anxiety, (7) Improved overall clinical impression. As part of the assessment of the achievement of the target result, in accordance with Order 46n of the Ministry of Health of the Russian Federation dated February 2, 2022 (Regulations on Clinical Approbation), a threshold of 85% was set. In terms of (1) Improvement in the subjective characteristics of sleep, (2) Improvement in the quality of sleep, (3) Decrease in the severity index of insomnia, (4) Decrease in daytime sleepiness, the target result was more than 85%, which is significantly higher compared to the control group. An assessment was made of the correspondence of the distribution of indicators to the normal law using the Kholmogorov-Smirnov criterion. Comparison of groups using methods of analytical statistics was carried out using Student's t-test for dependent samples and Mann Whitney's U-test for independent samples. The assessment of the correlation of quantitative results was carried out using the Pearson coefficient (r) for interval variables with a normal distribution. The results are considered to be significant at p<0.01. All obtained empirical values were in the zone of statistical significance. Evaluation of the data obtained in the course of clinical testing shows the effectiveness of the proposed clinical and psychological method for the treatment of insomnia.